(untitled) (Journal of the College of Languages (JCL), 2023)
The Iraqi Turkmen poet Falkoglu is considered a self made man who occupies a special place among the greatest Iraqi Turkmen poets in the twentieth century. No doubt, he left his fingure prints on his age despite the influence of the classical poetry (Al-Diwan poetry) in his poems. Moreover, the effects of Al-Saz poets are obvious in his poems. It is clear that he was a great popular poet whose poetry was about patriotism and religious values. His poetic styles were amazing. The poet loved his country as much as he loved his language. He started writing poetry on the concepts of love, nationalism, religion and wisdom. In addition to his other poems, the poet wrote a lot of Khweirat ( sung poems). He wrote classical poems as well as free modern pomes ( Al-Aroodh and Al-Hijaa). Moreover, the poet was influenced by our great poet Fudholi Al-Baghdadi. The present paper includes a comprehensive summary of the poet where we touched upon his life, his literary character, his poetry, popular poetry and homeland love. Country and nation love is the subject of our study since it comes first in his poetry. His poetry is transformed from the Iraqi Turkmen language into modern Turkish. I hope this study will be beneficial for researchers. ÖZET yüzyılın en başarlı Irak Türkmen şairleri arasında özgü bir yer tutan Felekoğlu şüphesiz yaşadığı yüzyıla damga vurmuştur. Şiirlerinde hem divan şirinin izi ve etkisi bulunduğu halde, saz şairlerinin izleride onun şiirlerinde ortaya çıkar ve büyük bir halk şairi olduğu da açıkca belirlenir. Çalışmamızın ana teması olan millet ve yurt sevgisinin anlayışı, şairin şiirlerinde oldukça derin duygular barındıran insanı hayrete düşüren bir üslupla önümüze çıkmaktadır. Millet ile yurt oldukça yoğun bir şekilde kasidelerinde işlenmiştir. yazdığı şiirlerin çoğunuda (lahut) felsefesini yaymak isteyen şair yurt severlik ve millet severlik konularını da unutmayan bir şairdir. Dilini sevdiği kadar yurdunu da severmiş. şiire sevda yoluyla geçmiştir. “Gazel, milli, dini hikmet lahut” alanlarında şiirler yazan şairin bir çok hoyratlarıda vardır. Aruz ve hece vezinleriyle şiirlerini yazan Felekoğlu, şiirlerinde büyük şairimiz Fuzulinin etkisinden bir türlü kurtulamamıştır. Bu çalışmamıza kapsamlı özetle başlıyoruz. Ondan sonra çalışmamızın öznesi olan Felekoğlunun hayatı, edebi kişiliği, eserleri, vatan ve millet tanımı, tȕrkmen edebiyatında halk şiirie, değindikten sonra şairin eserlerinde ön plana çıkan millet ve yurt severlik şiirlerini ele alıp Irak Türkmen dilinden yeni Türkçeye çevirıp açıklamaktayız. Bu çalışmanın araştırma yapacaklara da yararlı olacağı değerlendirilmektedir.